Associations between school lunch consumption and urinary phthalate metabolite concentrations in US children and adolescents: Results from NHANES 2003–2014. (December 2018) - Muñoz, Isabel; Colacino, Justin A.; Lewis, Ryan C.; Arthur, Anna E.; Meeker, John D.; Ferguson, Kelly K.
Abstract: Diet is a major route of phthalate exposure in humans due to use in food packaging materials. School lunches may be an important contributor to phthalate exposure in children and adolescents in the US because of the large amount of packaging necessary for mass-produced foods. We used 2003–2014 National Health and Nutrition Examination Survey data to study the association between school lunch consumption and urinary phthalate metabolite concentrations in children (ages 6–11 years, N = 2196) and adolescents (ages 12–19 years, N = 2314). After adjustment for other covariates, children who Always consumed school lunch had significantly elevated urinary concentrations of the following phthalate metabolites compared to levels in children who Never ate school lunch: sum of di(2‑ethylhexyl) phthalate metabolites, (28% higher, 95% confidence interval, CI: 10, 49%); mono‑(carboxy‑octyl) phthalate (MCOP; 43% higher, 95% CI: 17, 76%) and mono‑ n ‑butyl phthalate (18% higher, 95% CI: 3.5, 34%). We did not find statistically significant associations in adolescents, but the trend for MCOP concentrations was similar to that of children. In sensitivity analyses, associations between 24-hour recall of cafeteria food and urinary phthalate metabolites were not statistically significant, which could indicate that associations observed with Always consuming school lunch are due to residual confounding. Our findings show that children who Always eat school lunch had higher levels of exposure to some phthalates, but the source of differences in exposure need to be evaluated in additional studies. Highlights: We examined urinary phthalate metabolites by school lunch consumption categories. Children reporting Always eating school lunch had higher levels of some metabolites. Calories consumed from school cafeteria food were not associated with metabolites. No associations were observed between school lunch and phthalates in US adolescents. Further investigation of elevated phthalate exposure in children who Always eat school lunch is required.